Teori Belajar Behavioristik: Memahami Hubungan Stimulus-Respons dan Aplikasinya dalam Pendidikan serta Terapi Perilaku - Azima, Rizqiyul; Batubara, Juliana; Deliani, Nurfarida (Lembaga Yasin AlSys, 2025)
Behavioristic learning theory is an approach to psychology that emphasizes the importance of behavior that can be observed and measured objectively. This theory focuses on the relationship between stimulus and response, and emphasizes the role of the environment as a major factor in the formation of behavior. In behaviorism, learning is seen as a change in behavior that occurs due to reinforcement or punishment. The main figures in this theory include Ivan Pavlov with classical conditioning theory, B.F. Skinner with operant conditioning theory, and John B. Watson who popularized behaviorism as a scientific approach to psychology. Applications of this theory are widely used in education, training, and behavior therapy, especially in forming new habits or eliminating unwanted behaviors. The strength of this approach is its simplicity and focus on measurable results, while its weakness lies in its lack of attention to internal factors, such as motivation, emotions, and cognitive processes. By understanding behavioristic learning theory, educators and practitioners can design effective strategies to redirect behavior through environmental manipulation and appropriate reinforcement.